Study of methods for state regulation of prices and costs of the health care system for medicines in the United Kingdom - A. A. Leshkevich; D. S. Yurochkin; Z. M. Golant; I. A. Narkevich (IRBIS LLC, 2022)
Objective: analysis of state regulation of prices and costs for the purchase of medicines (drugs) in the United Kingdom (UK), and proposal development to improve the processes of state regulation of manufacturers' marginal registered prices of medicines included in the list of vital and essential drugs approved in the Russian Federation.Material and methods. Analysis of the structure of state regulation of prices and costs for the procurement of drugs was carried out based on information contained in the regulatory legal documents of the UK Government, health services and technical regulation, and data provided in systematic reviews and articles.Results. A key feature of regulation in the UK is maximizing the efficiency of health care costs based on the principles of digitization, long-term planning and health technology assessment in pricing. Government regulation of costs is focused on the patent-protected drug segment. Providers of such medicines fall under the Voluntary or Statutory Scheme and are required to make payments in the form of a fixed percentage of sales to the Department of Health and Social Care. Certain drug segments are exempt from payments to stimulate innovative development of the pharmaceutical industry and accelerate market access for new therapies. As practice shows, the Voluntary Scheme is more profitable for most companies. Regulation in the segment of reproduced drugs is carried out by free-market mechanisms and the antimonopoly service.Conclusion. The analysis revealed the mechanisms and key features of the methods of state regulation of prices and costs of the health care system for the procurement of drugs, identified best practices that are promising for adaptation to improve the state regulation of prices in the Russian Federation.